COPD clinical control as a predictor of future exacerbations: concept validation in the SPARK study population. Issue 4 (10th February 2020) - Barrecheguren, Miriam; Kostikas, Konstantinos; Mezzi, Karen; Shen, Steven; Alcazar, Bernardino; Soler-Cataluña, Juan José; Miravitlles, Marc; Wedzicha, Jadwiga A
Abstract : The concept of chronic obstructive pulmonary disease (COPD) control has been proposed to guide treatment decisions in COPD. In this study, we aimed to validate the prospective value of this concept in the SPARK study population. Control was assessed based on COPD stability and impact. Patients with low impact and stability during weeks 1–12 were classified as controlled, and exacerbations were measured during a 52-week follow-up. Of the 2044 patients included a majority were non-controlled (80%), frequently due to high impact. During the follow-up, the rate of moderate/severe exacerbations was significantly lower in controlled patients (rate ratio, 0.56, 95% CI 0.48 to 0.65 p<0.0001) and time-to-first moderate/severe exacerbation was significantly delayed. This study demonstrated an association between control status and risk of exacerbations.